2023
DOI: 10.1111/ecot.12355
|View full text |Cite
|
Sign up to set email alerts
|

Financial frictions, bank intermediation and monetary policy transmission in India

Abstract: Do the different types of financial friction have differential implications for monetary transmission in emerging economies? We investigate this question using India as the country for analysis. We adopt a New Keynesian business cycle model with bank intermediation, extend it by the Indian economy-specific features and validate with the data. The baseline model explains the co-movements of interest rates, incomplete pass-through and sluggish adjustment mechanism of the macro-financial variables for a policy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Most studies have found plausible effects 8 of monetary policy shocks during the MI targeting regime in India (Al Mashat, 2003;Aleem, 2010;Bhoi et al, 2017;Khundrakpam & Jain, 2012). On the contrary, there are others who have found no effect of monetary policy shocks on inflation and output during the same period (Banerjee et al, 2018;Bhattacharya et al, 2010;Mishra et al, 2016). Studies examining this effect have mainly relied on VAR frameworks (Aleem, 2010;Bhoi et al, 2017;Sengupta, 2014) that use Cholesky decomposition techniques (e.g., Eichenbaum & Evans, 1995;Grilli & Roubini, 1995;Sims, 1992) under which the monetary policy does not react to instantaneous changes in the exchange rate.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most studies have found plausible effects 8 of monetary policy shocks during the MI targeting regime in India (Al Mashat, 2003;Aleem, 2010;Bhoi et al, 2017;Khundrakpam & Jain, 2012). On the contrary, there are others who have found no effect of monetary policy shocks on inflation and output during the same period (Banerjee et al, 2018;Bhattacharya et al, 2010;Mishra et al, 2016). Studies examining this effect have mainly relied on VAR frameworks (Aleem, 2010;Bhoi et al, 2017;Sengupta, 2014) that use Cholesky decomposition techniques (e.g., Eichenbaum & Evans, 1995;Grilli & Roubini, 1995;Sims, 1992) under which the monetary policy does not react to instantaneous changes in the exchange rate.…”
Section: Review Of Literaturementioning
confidence: 99%